Mixed-Initiative Approaches to Global Editing in Slideware - Edge, Darren; Gulwani, Sumit; Milic-Frayling, Natasa; Raza, Mohammad; Saputra, Reza Adhitya; Wang, Chao; Yatani, Koji (CHI 2015 Conference on Human Factors in Information Systems, 2015)
Good alignment and repetition of objects across presentation slides can facilitate visual processing and contribute to audience understanding. However, creating and maintaining such consistency during slide design is difficult. In order to solve this problem, we present two complementary tools: (1) StyleSnap, which increases the alignment and repetition of objects by adaptively clustering object edge positions and allowing parallel editing of all objects snapped to the same spatial extent; and (2) FlashFormat, which infers the leastgeneral generalization of editing examples and applies it throughout the selected range. In user studies of repetitive styling task performance, StyleSnap and FlashFormat were 4-5 times and 2-3 times faster than conventional editing, respectively. Both use a mixed-initiative approach to improve the consistency of slide decks and generalize to any situations involving editing across disjoint visual spaces.